Safety and efficacy of renal denervation utilizing standard bidirectional EP catheter: preliminary Vietnamese findings - Tran Ba Hieu; Nguyen Ngoc Quang; Pham Manh Hung (Italian Journal of Medicine)
Renal denervation (RDN) is a safe and effective treatment for hypertensive patients. However, data on its use with standard electrophysiology catheters, particularly from low- and middle-income countries, are limited. This study aimed to evaluate the acute safety and short-term efficacy of RDN in hypertensive patients using standard EP catheters from Vietnam. A prospective study was conducted from May 2023 to May 2024 at the Viet Nam National Heart Institute, Vietnam. A total of 22 patients (mean age 52.87±19.86 years, 12 male) with resistant hypertension underwent RDN by utilizing a standard bidirectional steerable radiofrequency (RF) ablation catheter with a 7 Fr diameter (Abbott, Chicago, IL, USA). Low-power RF applications have been applied along the length of both renal arteries. Renal ultrasound, blood tests, and 24-hour ambulatory blood pressure (BP) were checked at baseline, at 1 month, and at 3 months following RF ablation. The success rate of the renal artery approach with a standard bidirectional EP catheter was 100% (22/22 patients). The mean reduction of 24-hour ambulatory BP, and ambulatory daytime BP were respectively -8.72/-6.04 mmHg and -8.00/-6.09 mmHg at 1 month and -15.59/-9.22 mmHg and -15.27/-10.18 mmHg at 3 months (p<0.05 for systolic and diastolic BP) with unchanged medication. No severe complications were reported during the procedure and follow-up. Our initial results indicate the safety and efficacy of RDN as shown by a significant reduction of mean 24-hour ambulatory BP in comparison to baseline during short-term follow-up.